Abdülganî En-Nâblusî Şerhi bağlamında İbnü’l-Fârız’ın Kasîde-i Tâiyye’sinde Seyr u Sülûk - Öteleş, Zeliha (My University, 2014)
ABDÜLGANî EN-NÂBLUSÎ ŞERHİ BAĞLAMINDA İBNÜ’L-FÂRIZ’IN KASÎDE-İ TÂİYYE’SİNDE SEYR U SÜLÛK İbnü’l-Fârız (576/ 1181- 632/ 1235)’ın Kasîde-i Tâiyye’si, Arap sûfî şiirinin zirvesi kabul edilmektedir. Asırlarca şerhedilen bu kasîdenin son klasik şârihi, Abdülganî en-Nâblusî (1050/ 1641-1143/ 1731)’dir. Nazmü’s-sülûk ismiyle de bilinen Kasîde-i Tâiyye’de sûfî şâir, rûhî seyrini nazmetmiştir. Bu sebeple çalışmadaki odak kavram, “seyr u sülûk” olarak belirlenmiştir. Çalışma, üç bölümden oluşmaktadır. Birinci bölümde, sûfî şâirin biyografisine yer veren sınırlı sayıdaki eserler derlenmiştir. Ayrıca İbnü’l-Fârız ve kasîdeleri hakkındaki akademik çalışmalara yer verilmiştir. İkinci bölümde, Tâiyye kasîdesinin ilk şârihi olan Fergānî (ö. 699/ 1300)’den Nâblusî’ye kadar olan şârihler ve eserlerinin yazma nüshaları aktarılmıştır. Ayrıca, Nâblusî ve sonrasında İbnü’l-Fârız beyitlerini şerh eden şârihlere ve şârihlerin yazma nüshalarına yer verilmiştir. Son bölümde ise Tâiyye kasîdesindeki beyitler tasnîf edilerek, Nâblusî şerhi bağlamında ele alınmıştır. Nâblusî’nin Tâiyye şerhi, sûfî metinler arasında husûsî bilgilere yer vermesiyle temâyüz etmiştir. Mânâ kapılarını okuyucunun isti‘dâdı nispetince aralayan bu şerh, son dönem İbnü’l-Fârız şârihlerinden Ali Salâhaddîn Yiğitoğlu (ö. 1939)’nun Türkçe tercüme ve şerhine esas teşkîl etmiştir. rız, Nâblusî, Tâiyye Kasîdesi, Tasavvuf

Seyr u Süluk in the Context of Abd al-Ghani al-Nablusi's Commentary on Ibn al-Farid's al-Qasida al-Taiyya Ibn al-Farid (576/ 1181- 632/ 1235) ‘s al-Qasida al-Taiyya is regarded as the summit of Arabic sufi poetry. The last classic commentator of this eulogium which is expounded for centuries is Abd al-Ghani al-Nablusi (1050/ 1641-1143/ 1731). The sufi poet has versified spiritual flow in al-Qasida al-Taiyya which is also known as Nazmü-s-süluk. Because of this reason, the main concept in our study is defined as “seyr u süluk’’. The study consists of three parts. In the first part; limited numbers of works which consist of the sufi poet’s biography are compiled. Moreover; the academic works about Ibn al-Farid and his eulogiums are included. In the second part; the commentators from Fergani (d. 699/ 1300) who is the first commentator of Taiyya eulogium to Nablusi, and their works’ manuscript copies are attached. However; the commentators that expounded Nablusi and after Ibn al-Farid verses, and their manuscript copies are included. In the last part; Nablusi is discussed within the context of his opinion, by classifying some verses of Taiyya eulogium. Nablusi’s Taiyya annotation came to the fore by including the essential information between the sufi works. This comment which provides to understand the significance based on readers’ abilities, constituted the basis for the Turkish translation and comment of Ali Salahaddin Yigitoglu (d. 1939) who was the one of last period Ibn al-Farid commentators. Ibn al-Farid, Nabulusi, al-Qasida al-Taiyya, Sufism
Keywords: İbnü’l-Fârız; İslam Dini; İslam Tasavvufu; Nâblusî; Tâiyye Kasîdesi; Tarih